Voter Turnout Analysis of Canadian Undergraduate Student Unions, 2016-2018 - Justin Patrick; Daniel Patrick; Oleksii Zahreba (Canadian Journal for New Scholars in Education)
Annual election turnouts of campus student unions from Canadian publicly funded universities are analyzed for the 2016, 2017, and 2018 academic years. This first quantitative study of its kind in a Canadian context assesses the current state of student democracy in these higher education institutions and explores potential indicators of higher turnout, including online voting versus paper ballot systems, electorate size, and percentage of part-time students. Descriptive statistics revealed that student union voter turnouts were generally low, averaging about 21% over the study period. A linear multiple regression is conducted to examine the significance of potential factors that could impact turnout. Online voting is found to have a significant impact on increasing voter turnout. Student unions with larger electorates and higher percentages of part-time students were found to experience more difficulty generating voter turnout, which suggests that these student unions need to adapt their election promotion strategies to reach their voters more effectively.